Increasing Interest in Learning by Applying Learning Summary Writing Skills Text Content Using Inspiring Stories Important Video Media for Student Class IX - Sari, Keisi Tiara; Risnawaty (International Journal of Educational Research Excellence (IJERE), 2024)
The skill of writing a summary of the contents of an inspirational story text is very important for students to simplify and clarify something too long. The higher the student's writing ability, the higher the level of understanding of what has been conveyed/listened to. However, most students lack mastery of summarizing. This research aims to increase students' interest in learning by implementing learning skills in writing summaries of the contents of inspirational story texts using illustrated video media in class IX Plus students at Al-Azhar Medan Middle School, Medan Johor District, academic year 2023-2024. The subjects of this research were class IX Plus students at Al-Azhar Medan Middle School, Medan Johor District, for the 2023-2024 academic year, consisting of 40 students. The sample in this study is defined as individuals/students who constitute the entire population studied. The method used in this research is classroom action research (PTK). The indicators for this research are teachers who teach the material to write summary sentences and paragraphs on the contents of inspirational story texts. The data analysis technique used was classroom action research through Cycle I and Cycle II. Through the stages: class action plan, implementation, observation, and reflection according to the learning implementation plan (RPP) and syllabus applicable in the learning curriculum at Al-Azhar Middle School Medan. Based on data from 40 students, it was found that the percentage of classical student learning completeness in cycle I was 75% of the number of students who completed it, while 10 students did not complete it, and in cycle II it was 95% of the number of students who completed it, there were 38 students who did not complete it, while 2 did not complete it.